Revitalization of Sabhara Patrol as a Preventive Measure Against Motorcycle Theft - Rampewali, Andi (Advances in Police Science Research Journal, 2024)
Research in background back by the rise of vehicle accidents in Bandung which triggered disruption of security and public order and led to public unrest. Therefore, research is needed that aims to describe the implementation of patrol conducted by Sabhara Polrestabes Bandung officers, and identify the forms of patrol efforts undertaken to prevent theft of motorized vehicle. Theories and concepts used to answer the problem are revitalization theory, situastional crime prevention theory, theft concept, sabhara patrol concept, and Collier management concept. The result found that the implementation of Sabhara patrol was analyzed with situational crime prevention theory and Collier management concept as well as prevention efforts carried out against motor vehicle theft were analyzed by Perkabaharkam Number 1 of 2017 concerning patrol and revitalization theory. Implementation and patrol efforts that have been carried out are still not optimal, the crime is still high. Based on the result of the study, the researchers suggest that re-evaluations be made related to motor vehicle theft the provision of AAP should be more systematic and directed, coordinate frequently with Bahbinkamtibmas officers, make officers’ pocket books containing patrol SOP, create android-based application that keep pace with the times, and make sticker brochures to make people recognize patrol officers in their environmentand make it easier for people to provide information quickly.